TINJAUAN KORELASIONAL ANTARA PERSEPSI KEPEMIMPINAN DAN MOTIVASI BERPRESTASI DENGAN KOMITMEN PROFESI GURU SMA NEGERI 27 TANGERANG - Suprijartono Suprijartono; Ruknan Ruknan (Derivatif : Jurnal Manajemen, 2017)
The problems relating to professional commitment among teachers who still lack the potential to be a constraint in the role of schools to promote the development of quality human resources. This study aims to determine the correlation between the perception of leadership and achievement motivation with professional commitment.The research method used is survey with population of  teacher in 27 state high school  Tangerang as many as 30 people. The entire population as a sample of the study. Data were analyzed with regression and correlation technique.Based on the results of research concluded among others: First, there is a positive correlation between leadership perceptions with professional commitment (ry1 = 0.743). Conceptually, if the teacher's perception of the principal's leadership is positive then it can increase professional commitment. Second, there is a positive correlation between achievement motivation and professional commitment (ry2 = 0,826). Conceptually, if the motivation of high achievement of teachers can increase the commitment of the profession. Third, there is a positive correlation between leadership perceptions and achievement motivation with professional commitment (Ry12= 0.84). Conceptually, if both the perception of leadership and achievement motivation of high teachers can increase the commitment of the profession.  Keywords: leadership perception, achievement motivation, professional commitment.